Spiroplasma Isolated From Third-Generation Laboratory Colony Ixodes persulcatus Ticks - Beliavskaia, Alexandra; Hönig, Vaclav; Erhart, Jan; Vyhlidalova, Tereza; Palus, Martin; Cerny, Jiri; Kozlova, Irina; Ruzek, Daniel; Palomar, Ana M.; Bell-Sakyi, Lesley (Frontiers in Veterinary Science, 2021)
Spiroplasma are vertically-transmitted endosymbionts of ticks and other arthropods. Field-collected Ixodes persulcatus have been reported to harbour Spiroplasma, but nothing is known about their persistence during laboratory colonisation of this tick species. We successfully isolated Spiroplasma from internal organs of 6/10 unfed adult ticks, belonging to the third generation of an I. persulcatus laboratory colony, into tick cell culture. We screened a further 51 adult male and female ticks from the same colony for presence of Spiroplasma by genus-specific PCR amplification of fragments of the 16S rRNA and rpoB genes; 100% of these ticks were infected and the 16S rRNA sequence showed 99.8% similarity to that of a previously-published Spiroplasma isolated from field-collected I. persulcatus. Our study shows that Spiroplasma endosymbionts persist at high prevalence in colonized I. persulcatus through at least three generations, and confirms the usefulness of tick cell lines for isolation and cultivation of this bacterium.